2016
DOI: 10.1016/j.apenergy.2016.07.088
|View full text |Cite
|
Sign up to set email alerts
|

The novel use of phase change materials in an open type refrigerated display cabinet: A theoretical investigation

Abstract: In this paper, 2D CFD models have been developed for a prototype refrigerated open type multi-deck display cabinet with and without integrated phase change material (PCM). The models can predict the effect of adding a PCM container on cabinet efficiencies, air temperature distributions, product temperatures and air flow patterns inside the cabinet at a range of operating conditions including space air temperatures and evaporator air velocities. To validate the cabinet models, the prototype cabinet was mounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These results indicated that the cooling rate improved with velocity increasing; the cooling range was between 2.05 and 2.95 • C from 5 to 45 min. The cooling capacity release rate of the storage module was affected by forced convection and thermal conductivity [52], and the cooling capacity released in a certain period was limited. When air velocity was low, the cooling capacity taken away from the storage area was lower than the cooling capacity released by the storage module, resulting in a high outlet temperature of the fan, thus affecting the cooling rate in the cargo area.…”
Section: Inlet-velocity Influencementioning
confidence: 99%
“…These results indicated that the cooling rate improved with velocity increasing; the cooling range was between 2.05 and 2.95 • C from 5 to 45 min. The cooling capacity release rate of the storage module was affected by forced convection and thermal conductivity [52], and the cooling capacity released in a certain period was limited. When air velocity was low, the cooling capacity taken away from the storage area was lower than the cooling capacity released by the storage module, resulting in a high outlet temperature of the fan, thus affecting the cooling rate in the cargo area.…”
Section: Inlet-velocity Influencementioning
confidence: 99%
“…Most of them optimize ORDC when it was full with package. The structure [5,6], the air guiding strip [2], and the phase change material (PCM) [3,4] can be found to improve the ORDC performance. For example, Wu et al [5] discussed the effect of porosity of the perforated back panel (PBP) (0% -7%) on average temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental advantage of combining PU foam-MPCM in cold storage is the high storage capacity over a small temperature range and greater energy efficiency. As a result, researchers have looked into incorporating PCM into cold energy storage sectors such as solar power air conditioning systems, 20 supermarket refrigeration, 21 direct application of PCM in cold storage vans, 22 beverage coolers 23 and bottle coolers. 24 The polyacrylic shell material is used in many studies because of its compatibility with organic PCM and paraffin is the material of choice because of its excellent thermal conductivity, availability, cost-effectiveness and appropriate phase change temperature range for cold energy storage applications.…”
Section: Introductionmentioning
confidence: 99%